Rent-a-girlfriend. Volume 11 - Miyajima, Reiji (Kodansha Comics, 2021)
"A girlfriend showdown! Ruka crashed Kazuya's birthday party in the hopes of appealing to the Kinoshita family and proving that she was a superior girlfriend candidate to Mizuhara. Everything seemed to be going her way at first. Even Kazuya's grandmother was warming up to her. That all changes when Mizuhara arrives to steal the spotlight, however. Down but not out, Ruka is still determined to secure her place as Kazuya's one and only girlfriend! Can the boneheaded Kazuya weather the storm of a woman in love? Page [4] of cover.